D6.12 Report on the extroversion programme activities - Hadjimitsis, Diofantos G.; Fotiou, Kyriaki; Pittaki-Chrysodonta, Zampela; Schreier, Gunter; Kaskara, Mariza; Alatza, Stavroula; Papakonstantinou, Maria; Fountoulakis, Ilias; Tsoumas, Ilias; Mpothos, John; Sitokonstantinou, Vasilis; Salta, Fotini; et al. (My University, 2023)
This deliverable presents the review of the actions regarding extroversion that took place during RP3. The extroversion programme aims to upscale the Eratosthenes Centre of Excellence strategic positioning to address regional and European challenges to broaden the horizons of the Eratosthenes Centre of Excellence’s staff, to attend international events for shaping the Eratosthenes Centre of Excellence strategy and perform ad-hoc trainings and discussions with professionals in industries. The report includes detailed information of the activities that were undertaken, including: ● Lectures by invited speakers. ● (Virtual) workshops organized by the Eratosthenes Centre of Excellence ● Other activities, such as conference attendance, meetings with stakeholders of the Eastern Mediterranean, Middle East and North African (EMMENA) region, trainings etc.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; capacity building